2015
DOI: 10.3151/jact.13.275
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Chemical Composition and Physical Properties of C-S-H Generated from Cementitious Materials

Abstract: Calcium silicate hydrate (C-S-H) is a dominant hydration product of cementitious materials. Therefore, its chemical composition and physical properties affect the performance of concrete. The purpose of this study is to investigate the chemical composition (CaO/SiO 2 molar ratio (Ca/Si ratio), and H 2 O/SiO 2 molar ratio (H 2 O/Si ratio)) and physical properties, such as density and specific surface area, of C-S-H. These factors are measured using synthesized C-S-H samples and C-S-H generated from various ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…In this study we used an upper estimate for the surface area of C-S-H 1.5 which was based on experiments at Ca/Si = 1.4. (Suda et al, 2015). The surfacenormalized mean K d value seems to increase with increasing Ca/Si ratio of the C-S-H phases but the trend is statistically not significant.…”
Section: Fe Sorption On C-s-hmentioning
confidence: 79%
“…In this study we used an upper estimate for the surface area of C-S-H 1.5 which was based on experiments at Ca/Si = 1.4. (Suda et al, 2015). The surfacenormalized mean K d value seems to increase with increasing Ca/Si ratio of the C-S-H phases but the trend is statistically not significant.…”
Section: Fe Sorption On C-s-hmentioning
confidence: 79%
“…The more complex scenario for pore structure and local densities emerging from our study suggests a different origin of the S sp values. Recent studies (8,46) point to differences in the drying conditions and have shown that, only in oven-dried C-S-H at 100°C under vacuum, the water of all C-S-H pores (gel and capillary) is completely removed, leaving only water molecules in the nanotexture. In these conditions, the measured specific surface area of C-S-H (using water as an adsorption probe) is S H2O sp = 200 − 300 m 2 =g.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Validity of the phase composition For the purposes of verifying the validity of the phase composition determined in the present study, the amount of combined water was estimated from the phase composition by referring to the previous researches (Maruyama and Igarashi 2014; Suda et al 2015). Using the molar weight of combined water, which is shown in Table 4, and the amount of each hydration product determined by Rietveld analysis, the amount of combined water contained in each hydration product contained in the 11% RH dried sample in this study was calculated.…”
Section: Effect Of Phase Composition On Expansion Characteristicsmentioning
confidence: 91%